HUBUNGAN KETEPATAN PEMBERIAN MAKANAN PENDAMPINGASI DENGAN PERKEMBANGAN BAYI USIA 9-12BULANDI DESA WATESUMPAK KECAMATANTROWULAN MOJOKERTO - Ratnaningsih, Tri; Murti Utami, Titis (JURNAL KEPERAWATAN SEHAT, 2015)
Breast milk’s food supplement is a supplement which is given during 6-24 months old for completed babies’ nutrition that have not gotten from Breast milk. But there is mother gives Breast milk’s supplement early and lately who was not proper by time, type, frequency and quantity decided. Therefore, the gift of Breast milk’s food supplement affects the babies’ growth such as hard motoric, soft, social and independence. This research went for proving the relation of Breast milk’s food supplement precison with babies’ growth 9-12 months old in Watesumpak Trowulan Mojokerto. In research used analytical observational designed by case control. There whose 39 respondents are taken by total sampling. Data collection used Breast milk’s food supplement questionnaire and Pre Screening Development Questionnaire. This research used presentil with cross tab data analysis, so it can be concluded that the hypothesis of this research can be said that there tendency in relation of giving Breast milk’s food supplement accuracy with babies growth of 9-12 months old in Watesumpak Trowulan Mojokerto. Giving Breast milk’s food supplement well in time, type, frequency and quantity can be influenced by education, proffesion, earning, information, society and families’ supports. These support the process of babies’ growth because it is important progress in constructing the structure and the function of babies body so that the nutrition of babies with its growth must be balanced to reach the proper growth.Keywords:Breast milk’s supplement food, Growth, 9-12 months old babies